God, the beautiful and mathematics: A response - Smit, Peter-Ben (HTS teologiese studies, 2021)
Volker Kessler (‘God becomes beautiful … in mathematics’ – HTS 2018) argues two points to Rudolf Bohren’s list of four areas where (1) God becomes beautiful should be extended with a fifth one: mathematics and (2) mathematics can be argued as a place where God becomes beautiful. In this response, we would like to argue that (1) the extension of Bohren’s list that Kessler argues in favour of is superfluous and (2) that Kessler makes a number of questionable assumptions about (the philosophy of) mathematics. By arguing against Kessler, we intend to make an interdisciplinary contribution to the discussion about the relationship between mathematics and theology by pushing the debate into direction of a more careful consideration of mathematics as an area in which God’s beauty may become apparent.Contribution: Contributing to the interdisciplinary exploration of theology in HTS Teologiese Studies/Theological Studies, this article further develops the consideration of the fundamental theological topic of God, the beautiful and mathematics as it was proposed in this journal by Volker Kessler, by discussing it from a systematic theological and mathematical perspective.